Pendugaan Kerapatan Vegetasi dan Cadangan Karbon di HLG Sungai Buluh Jambi menggunakan NDVI - Istomo; Indra Putra, Erianto; Meyrista Sekar Agta Putri, Nindhy (Journal of Tropical Silviculture, 2025)
Sungai Buluh Peat Protection Forest (HLG) is a peat protected area in Jambi that still natural and characterized by a high degree of vegetation density. This study aimed to estimate vegetation density using the Normalized Difference Vegetation Index (NDVI), estimate biomass and carbon stock along with fire hazard levels, and analyze the relationship between NDVI, vegetation diversity, and carbon reserves in HLG Sungai Buluh. The methods used include vegetation analysis, carbon estimation using allometric and destructive testing for seedlings and understory plants, fire hazard level estimation using land cover scoring and NDVI values. The result showed NDVI was categorized into three classes, nemely class 1 (-0,015 – 0,369), class 2 (0,369 – 0,438), class 3 (0,438 – 0,633). The most families found were Lauraceae, Dipterocarpaceae, and Myrtaceae. The average biomass and carbon stock obtained were 191,26 tons/ha and 89,90 tons C/ha, respectively. Fire hazard levels in all classes were found to be high. Carbon stock strongly correlated with LBDS (r = 98,2%). The NDVI value strongly correlated with the number of species.